Inclusivity of Pre-Learning Screening for Religious and Moral Values in Early Childhood Education (PAUD) - Pratiwi, Dewi; Mufid; Afrianingsih, Anita; Rohman, Zulia (Universitas Pendidikan Ganesha, 2025)
Moral degradation of children in the era of technological revolution has a negative impact and can even affect the social life of society. Because of the importance of children's morals before introducing science, they need to be accustomed to manners in order to form good character. Early childhood is a critical period in human development including character formation. This study aims to develop an inclusive pre-learning screening instrument, focusing on religious and moral values in Early Childhood Education (PAUD). This study uses the Research and Development (RnD) method, with development carried out on an instrument that initially only functioned to assess the physical aspects of children. In order to realize a more comprehensive approach, the instrument developed includes a holistic assessment of the development of religious and moral values in early childhood. The subjects of this study involved 25 people, consisting of 10 teachers and 15 parents. Data were obtained through interviews, observations, and questionnaires used to measure the effectiveness of the instrument in identifying children's readiness in learning religious and moral values. The results of the study indicate that the instrument developed can provide a more complete picture of child development, and is able to facilitate a more inclusive learning process in the PAUD environment. These findings are expected to contribute to the development of assessment instruments in PAUD, especially in the religious and moral aspects, as well as encourage the implementation of more inclusive instruments for children with various backgrounds.